Fenomena Hoax dalam Al-Qur’an Perspektif Tafsir Maqasidi - khoiriah siregar (Institut Agama Islam Negeri Padangsidimpuan, 2020)
AbstractThe rapid development of information technology makes the phenomenon of hoaxes more widespread and spread rapidly. Basically, in this sophisticated era, all information that is true and not, is of course easily obtained through internet access (social media) which is already familiar to all people, especially in Indonesia. For that, as good Muslims, we should wisely use social media and we need to clarify in advance the information that we can receive and share with the public. This paper discusses the phenomenon of hoaxes in the Koran by using the perspective of maqasidi interpretation. The method used is a qualitative research method or library research with maqasidi interpretation approach. As for the conclusions that can be drawn from this paper, among others: First, in responding to the widespread phenomenon of hoaxes, it can be anticipated wisely in using social media and in disseminating news, it should first overlap or clarify and be selective in sharing the news. Second, things that can be done by a good Muslim to face and anticipate the occurrence of hoax phenomena are hifz al-‘aql (salvation of reason), hifz al-nafs (salvation of souls) and hifz al-daulah (nationalists).